207 ESOPHAGEAL BIOPSY AND SWAB MICROBIAL CHARACTERIZATION WITH HEALTH AND ESOPHAGEAL DISEASE IN CHINA. (14th September 2020) - Li, M; Shao, D; Song, G; Meng, F; Hao, C; Li, X; Wei, W
Abstract:  : Little is known about the esophageal microbiota and esophageal health or disease in China, especially esophageal squamous cell precancerous lesions. And there is currently no optimal sampling method for esophageal microbiota. Consequently, we compared microbial signature between and within esophageal biopsy and swab specimens from participants in healthy or with esophageal diseases. Methods: A total of 236 subjects were recruited in the Linxian Cancer Hospital (Henan, China), including 5 groups as 70 healthy cases, 70 esophagitis cases, 70 low grade intraepithelial neoplasia (LGIN) cases, 19 high grade intraepithelial neoplasia (HGIN) cases and 7 esophageal squamous cell carcinoma (ESCC) cases. Sterile biopsies and swabs were used to collect paired samples from the same participants under the endoscopy examination. DNA was extracted with the MoBio PowerSoil Kit. Data from 16S rRNA gene sequencing were processed using QIIME2 and R to evaluate differences in alpha and beta diversity and taxonomic relative abundances. Results: Alpha diversity was not significantly different between specimens (biopsy = 116.2, swab = 118.0, P > 0.05). In swabs, there were differences of observed OTUs among groups but not Shannon index, detailly, there was an inconspicuous decreasing from Health (125.0) to ESCC (114.0). About beta diversity, no distinct clustering by specimen was observed for weighted Unifrac distance and unweighted Unifrac distance. The 10 dominant genera were similar between specimens and among groups. Specially, Streptococcus was the most abundant except ESCCs; Fusobacterium was in the top ten only in ESCCs. And there was a decreasing of Prevotella 7 and an increasing of Haemophilus as progression. Conclusion: Esophageal biopsy and swab specimens could yield similar bacterial composition. Both can be used to find clues of microbiota and disease. And esophageal microbial composition and progression characterizations could provide new idea and basis for large scale, prospective cohort studies in the future.